Current and emerging therapeutic strategies for amyotrophic lateral sclerosis: from pharmacological approaches to gene and stem cell therapies - Wang, Ze; Huang, Jiajun; Yun, Di (Frontiers in Neurology, 2026)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that involves upper and lower motor neurons, severely impairing patients’ quality of life. The complex interaction of genetic and environmental factors in ALS pathophysiology complicates therapeutic development. Currently available disease-modifying pharmacological therapies for ALS offer limited efficacy, only slowing disease progression to a modest degree. The recent market withdrawal of a previously approved therapy (AMX0035) further underscores the challenges in this field. Biological targets for ALS and related neurodegenerative diseases offer a unique avenue for therapeutic intervention. With the advancement of genetic engineering technology, innovative therapies such as Stem cell therapy and gene therapy are also discussed, offering a promising horizon for ALS treatment. In addition, the management of ALS symptoms plays a key role in improving the daily lives of people with the disease. In this review, we summarize various strategies for treating ALS, providing an overview of the disease.